Extraction and Characterization of Forest Anchomanes (Anchomanes difformis (Bl.) ENGL.) Starch for Fuel Production - Adeosun Yetunde Mayowa; Adeoti Olusegun; Adeyanju Oluremi Opeyemi; Fatoye Abiodun Olaniyi; Ogunnaike Aderoju Funmilayo; Oyelayo Ajamu Oyedele (Turkish Journal of Agriculture: Food Science and Technology)
The use of cassava for fuel ethanol production in Nigeria is supported by the Nigerian Biofuel Policy and Incentives (NBPI) of 2007. Because of its food, feed and industrial value, the need to replace cassava with crops/plants that are food and feeds neutral has motivated this research. Starch was extracted from forest anchomanes (FA) (Anchomanes difformis (Bl.) ENGL.) tubers and some of its physicochemical and elemental properties were determined. At present, the plant is uncultivated in Nigeria and other parts of Africa where it is found. Results showed that the starch content in FA tubers varied from 72.12 to 75.83%. Starch granules from all parts of the FA tubers had similar proximate, antinutrients and elemental properties and appeared usable for fuel ethanol production. However, to suggest its potential to sustainably replace cassava, further investigations are needed beyond these initial results.